2015
DOI: 10.3109/01612840.2014.982842
|View full text |Cite
|
Sign up to set email alerts
|

‘Because That's the Way It's Always Been Done’: Reviewing the Nurse-Initiated Rules in a Mental Health Unit as a Step Toward Trauma-Informed Care

Abstract: Acknowledgement of the effects of trauma in the lives of the mental health service user population is increasingly being recognised as an imperative for Mental Health services. 'Trauma-informed care' provides values to guide practice. Mental Health nurses are well placed to commence integrating trauma-informed care into everyday practice. This paper describes the process of reviewing the nurse-led rules in an acute inpatient mental health unit as one step toward providing a trauma-informed environment. Finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(50 citation statements)
references
References 24 publications
1
49
0
Order By: Relevance
“…; Elliot et al . ; Goetz & Taylor‐Trujillo ; Isobel ; Lietz ). The date range for the studies spanned 2008–2015, and two Australian studies were included (Ashmore ; Isobel ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…; Elliot et al . ; Goetz & Taylor‐Trujillo ; Isobel ; Lietz ). The date range for the studies spanned 2008–2015, and two Australian studies were included (Ashmore ; Isobel ).…”
Section: Methodsmentioning
confidence: 99%
“…; Goetz & Taylor‐Trujillo ; Isobel ; Lietz ). The date range for the studies spanned 2008–2015, and two Australian studies were included (Ashmore ; Isobel ). Only one Australian study was found that examined TIC from the consumers’ perspective in an acute adult mental health unit (Isobel ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nurses are required to simultaneously engage with consumers and build rapport while delivering at times unwanted medication, keeping doors locked and enforcing rules (Isobel 2015). A Practice Development approach was used to allow the unit to develop its own meaning of TIC in practice.…”
Section: Implementing the Model: The Processmentioning
confidence: 99%